THE LIFE SKILLS CURRICULUM AT MA TECHNONATURA IN TERMS OF HARD SKILLS IS BASED ON STEM EDUCATION WHICH REFERS TO 21ST CENTURY SKILLS - Armai Arief; Dede Rosyada; Ahmad Sujai; Alip Nuryanto; Muammar Zulfiqri (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
Madrasah Technonatura is one of the Islamic-based educational institutions that seeks to adopt the historical progress of medieval Islamic civilization, which is the foundation of research at Madrasah Technonatura. The curriculum used in Madrasah TechnoNatura is based on KTSP 2006 content standards coupled with self-developed content standards taken from 21st century skills, which include 4C and 3R. The 4Cs are critical thinking, creativity, collaboration, and communication, while the 3Rs are reading, writing, and arithmetic, with the addition of 1C and 1R, namely Concordance Work and Religion. This research uses descriptive research methods, with researchers carrying out interview activities and using general guidelines about the information needed from key informants who provide informative data according to research needs. The life skills curriculum at MA Technonatura in terms of hard skills is based on STEM education, which refers to 21st century skills with a learning process based on First Global Challenge (FGC), Internet of Things (IoT), IOS Game Development, Smart Ecosystem, Arduino Weather Balloon, and Tissue Culture (Orchid), which is able to foster and develop students' life skills. In the category of soft skills, MA TechnoNatura builds and familiarizes the school culture with the implementation of dhuha prayer, tadarrus, learning Islamic religious lessons in the morning, and praying together.